New installation for inclined EAS investigations - Zadeba E.A.; Ampilogov N.V.; Barbashina N.S.; Bogdanov A.G.; Borisov A.A.; Chernov D.V.; Dushkin L.I.; Fakhrutdinov R.M.; Kokoulin R.P.; Kompaniets K.G.; Kozhin A.S.; Ovchinnikov V.V.; et al. (EPJ Web of Conferences, 2017)
The large-scale coordinate-tracking detector TREK for registration of inclined EAS is being developed in MEPhI. The detector is based on multiwire drift chambers from the neutrino experiment at the IHEP U-70 accelerator. Their key advantages are a large effective area (1.85 m2), a good coordinate and angular resolution with a small number of measuring channels. The detector will be operated as part of the experimental complex NEVOD, in particular, jointly with a Cherenkov water detector (CWD) with a volume of 2000 cubic meters and the coordinate detector DECOR. The first part of the detector named Coordinate-Tracking Unit based on the Drift Chambers (CTUDC), representing two coordinate planes of 8 drift chambers in each, has been developed and mounted on opposite sides of the CWD. It has the same principle of joint operation with the NEVOD-DECOR triggering system and the same drift chambers alignment, so the main features of the TREK detector will be examined. Results of the CTUDC development and a joint operation with NEVOD-DECOR complex are presented.